2016
DOI: 10.1159/000452821
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Banking

Abstract: Human milk banks play an essential role by providing human milk to infants who would otherwise not be able to receive human milk. The largest group of recipients are premature infants who derive very substantial benefits from it. Human milk protects premature infants from necrotizing enterocolitis and from sepsis, two devastating medical conditions. Milk banks collect, screen, store, process, and distribute human milk. Donating women usually nurse their own infants and have a milk supply that exceeds their own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 40 publications
2
112
0
10
Order By: Relevance
“…It is also documented that health professionals play an impor- This study revealed that informal milk sharing is done in some communities, although it is not a common practice. History of human milk banking indicates that establishment of HMBs was actually preceded by practices such as wet nursing and informal milk sharing (Haiden & Ziegler, 2017). That donation of breast milk is happening in some communities although informally, and hence not a totally new idea, could strengthen the HMB advocacy messages.…”
Section: Discussionmentioning
confidence: 99%
“…It is also documented that health professionals play an impor- This study revealed that informal milk sharing is done in some communities, although it is not a common practice. History of human milk banking indicates that establishment of HMBs was actually preceded by practices such as wet nursing and informal milk sharing (Haiden & Ziegler, 2017). That donation of breast milk is happening in some communities although informally, and hence not a totally new idea, could strengthen the HMB advocacy messages.…”
Section: Discussionmentioning
confidence: 99%
“…Schanler et al [36] did not find an effect on NEC in their blinded randomized controlled trial, but the most recent blinded randomized controlled trial did find a significant association between donor milk and the incidence of NEC [37]. These developments, the cost-effectiveness of human donor milk [38], and the potential benefits in the long term will probably lead to a policy where the use of preterm formula will only be limited to those infants of whom the parents do not want to use donor milk [39][40][41]. New techniques of pasteurization will increase the effectiveness of donor milk [42].…”
Section: Donor Milkmentioning
confidence: 98%
“…The practices to support the donation of human milk are now included among those proven to be effective for the protection and promotion of breastfeeding [15][16][17][18]. It is widely demonstrated that the two things enhance each other and contribute to the improvement in a synergistic way of child health and survival, precisely through the exclusive feeding of all newborns, even the most vulnerable, with human milk [9][10].…”
Section: Introductionmentioning
confidence: 99%